Il francoprovenzale della Puglia - Perta, Carmela (Linguistik Online, 2025)
The aim of this contribution is to describe and analyse the Apulian Francoprovençal variety spoken in Faeto and Celle San Vito from both an internal and external perspective. After introducing the communities under investigation from a historical-economic point of view, we will focus on descriptive elements of the Apulian Francoprovençal system that present variability in the linguistic uses of the speakers. Subsequently, the vitality of the alloglossia will be presented in a diachronic perspective, reporting also the initiatives undertaken by the communities in order to revitalise their ethnic language.